2017
DOI: 10.3390/nu9090961
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Intakes of Victorian Schoolchildren Measured Using 24-h Urinary Iodine Excretion

Abstract: Mandatory fortification of bread with iodized salt was introduced in Australia in 2009, and studies using spot urine collections conducted post fortification indicate that Australian schoolchildren are now replete. However an accurate estimate of daily iodine intake utilizing 24-h urinary iodine excretion (UIE μg/day) has not been reported and compared to the estimated average requirement (EAR). This study aimed to assess daily total iodine intake and status of a sample of primary schoolchildren using 24-h uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…We found that children had the highest median UIC, the highest usual iodine intake and the lowest probability of inadequate iodine intake. Adequate iodine nutrition has been reported in school-age children in Sweden [ 44 ], Portugal [ 45 ], and Australia [ 46 ] and a number of countries globally, simultaneously to finding inadequate iodine status in pregnant women in the same populations [ 16 , 47 , 48 , 49 ]. As milk is a main iodine source in countries without mandatory salt iodization, higher consumption of milk and dairy products in younger age groups explains why children are iodine sufficient while their mothers are not.…”
Section: Discussionmentioning
confidence: 99%
“…We found that children had the highest median UIC, the highest usual iodine intake and the lowest probability of inadequate iodine intake. Adequate iodine nutrition has been reported in school-age children in Sweden [ 44 ], Portugal [ 45 ], and Australia [ 46 ] and a number of countries globally, simultaneously to finding inadequate iodine status in pregnant women in the same populations [ 16 , 47 , 48 , 49 ]. As milk is a main iodine source in countries without mandatory salt iodization, higher consumption of milk and dairy products in younger age groups explains why children are iodine sufficient while their mothers are not.…”
Section: Discussionmentioning
confidence: 99%
“…Random spot urine (RSU) was chosen by selecting the maximal figures among the randomly generated number of each participant's all urinary samples. A complete collection of 24-hour urine sample met the following three requirements: (1) the total volume of 24 hour mixed urine ≥500 mL (19) ; (2) leakage of each spot urine ≤200 mL; and (3) missing no more than 1 void during collection.…”
Section: Urine Collection and Laboratory Testingmentioning
confidence: 99%
“…The data for this study were taken from the Salt and Other Nutrient Intake in Children study, a cross-sectional study conducted in a convenience sample of Victorian primary schools from June 2010 to May 2013. The main outcomes of the Salt and Other Nutrient Intake in Children study (31) and findings related to iodine intakes (26) have been previously published.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…The method for determining urinary Na has been described previously (33) . Urinary iodine concentration (μg/l) was determined using a modification of the method of Pino et al (26,44) . The internal standard used was a pooled urine sample (mean (SD) iodine concentration 84•1 (SD 3•8) μg/l) which gave a CV of 4•5 % (n 54).…”
Section: Urinalysismentioning
confidence: 99%
See 1 more Smart Citation